Recondite Etkin - Rodríguez, Edgardo José (Universidad Nacional del Litoral, 2022)
In this work we analyze structurally the piece Recóndita armonía (1987) by Mariano Etkin (1943-2016) and the aesthetic framework that surrounded it based on the composer´s writings of the same period. The study argues that the aesthetic-technical oppositions that can be inferred from them (e.g., linearity-nonlinearity, dialectical form-spatialized form) do nota have a direct correlate in the work in which the organic conception of pitch and rhythmic discontinuities are integrated, at different levels of the structure.